(untitled) (Comprehensive Journal of Science, 2025)
This study aims to measure beneficiaries’ satisfaction with the services of Al Zawiya Central Municipality in light of administrative quality principles, through analyzing perceived service quality dimensions and identifying key strengths and weaknesses in public service delivery, The descriptive method was applied and a questionnaire was used to collect data from a sample of beneficiaries covering dimensions of tangibles reliability responsiveness assurance and empathy, The findings indicated that overall satisfaction ranged from moderate to high with strengths related to processing speed and service interaction while some weaknesses appeared such as limited digital development and weak communication in certain departments, The study recommends enhancing digital transformation improving staff competencies and strengthening monitoring and complaint systems to improve municipal service quality.